Analysis of reflectometric measurements losses of spliced single mode telecommunication fibers with significantly different parameters - Ratuszek, Marek (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
In this paper there have been presented theoretical and basing on experiments analysis of one-way and two-way reflectometric measurements of spliced single mode telecommunication fibers with different refractive index profiles, received in various combinations of joints. In the analysis the dependence of one-way and two-way reflectometric measurements of splice loss on the mode field radii quotient and on the shift of axes of the spliced fibers as a function of measurement wavelength has been taken into account. On the basis of one-way reflectometric measurements a method explicitly proving the existence of a transient area in the spliced fibers has been presented.
Optica Applicata, Vol. 35, 2005, nr 2, s. 347-363
Keywords: optyka; reflectometry; fibers